BURNOUT SYNDROME, DEPRESSION, ANXIETY AND SUICIDE IDEATION IN PUBLIC SECURITY SERVERS - Soares, Wellington Danilo (2021)
The study aimed to evaluate the prevalence of Burnout Syndrome, depression, anxiety and suicidal ideation in public security workers who work in Minas Gerais. This is a descriptive research, with a quantitative, comparative and transversal approach. The sample consisted of 80 public security officers, male (81,3%) and female (18,7%), including socio-educational agents, military police, prison officers, military firefighters and civil police, chosen at random and who accepted to participate voluntarily in the research. Beck's anxiety, depression and suicidal ideation inventories and Maslach's Burnout inventory were used as instruments, with a descriptive statistic using the Statistical Package for the Social Sciences. A low prevalence rate of depression, suicidal ideation was found and anxiety among the participants, however the results are not unanimous and considering the employees in a unique way, it is possible to perceive the presence of the psychological sufferings mentioned in a smaller portion of the sample. Regarding the Burnout Syndrome, it was evident that the characteristics of emotional exhaustion and depersonalization showed low prevalence, since work involvement was considered low for most workers, being a factor that contributes significantly to the occurrence of such a syndrome. Despite the prevalence of the researched psychological disorders present low among the participants, the individual analysis shows the prevalence of these sufferings in some professionals, reinforcing that the work stress is experienced in a unique way by each one, being able to evolve to a disorder or be reframed.